The Swiss Circle of Magallanes: European Architecture in Chilean Patagonia - Correa-Baeriswyl, M (Institute of Physics Publishing, 2019)
In recent years, legal protection of buildings and sites in Chile has increased. Also different initiatives regarding cultural heritage have been developed through public financing, at both regional and national levels. An appreciation of architectural heritage has achieved an important role in the country. This article presents the results of historical research, regarding the headquarters of the Swiss Circle of Magallanes. This building was constructed in the 1920s in Chilean Patagonia, in the city of Punta Arenas. The organization of both the Swiss Circle and its building are part of the city s history related to the European immigration that took place in the region during the second half of the 19th century and the beginning of the 20th century. The immigration process in Chilean Patagonia was led by means of colonization policies, by the national government. The aim of these policies was to consolidate the occupation and development of this remote territory, historically hard to populate. The distance from populated economic centers, as well as the cold weather and difficulties for agriculture were the factors that made these lands hard to be effectively occupied. Immigrant groups arrived at Punta Arenas from different European nations. Italians, British, French, Spanish, Croats, Germans and Swiss were some of the nationalities that arrived to the city; some of them were organized according to the official settlers groups. It is possible to determine the arrival of Swiss settlers to Punta Arenas since the second half of the 19th century. The establishment of the Swiss Mutual Aid Society in 1902, and the creation of the Swiss Circle in 1920, reflected the social organization of Swiss settlers and their descendants, many of whom stayed in the region. This social organization finally materialized in the construction of the headquarters of the Swiss Circle of Magallanes, still preserved nowadays. The Swiss Circle was built of timber following the European concepts related to traditional Swiss chalets. This building represents the adaptation of foreign ideas and styles to a local context, related to the international immigration in Magallanes. For almost a century, the Circle has served the Swiss community and the residents of Punta Arenas. Even though, some interventions have modified the building over time, the original design still remains, and it can be recognized as a Swiss chalet located in this southern Chilean city. The Swiss Circle of Magallanes bears witness to the colonization efforts made in Chilean Patagonia since the second half of the 19th century, as well as the complex social settlement process of immigrant groups at that time. This building also represents an interesting synthesis that combines foreign and local building techniques and styles. Nowadays, the Swiss Circle is a space for cultural dispersion of Swiss traditions and it is materially and immaterialy deep-rooted in the local memory. This building relates to the Chilean national history of territorial occupation, and it is a relevant part of the city s special character, built upon by immigration. In recent years, the Swiss Circle has been recognized as an official heritage and efforts have been made locally to plan for its future restoration. © Published under licence by IOP Publishing Ltd.